Evaluating environmental risk assessment models for nanomaterials according to requirements along the product innovation Stage-Gate process. Issue 2 (7th January 2019) - Sørensen, Sara Nørgaard; Baun, Anders; Burkard, Michael; Dal Maso, Miikka; Foss Hansen, Steffen; Harrison, Samuel; Hjorth, Rune; Lofts, Stephen; Matzke, Marianne; Nowack, Bernd; Peijnenburg, Willie; Poikkimäki, Mikko; et al.
Abstract : A quantitative approach to matching existing environmental assessment models to the needs of stakeholders at different stages during innovation of nanomaterials and nano-enabled products. Abstract : Nanomaterial risk governance requires models to estimate the material flow, fate and transport as well as uptake/bioavailability, hazard and risk in the environment. This study assesses the fit of such available models to different stages during the innovation of nano-enabled products. Through stakeholder consultations, criteria were identified for each innovation stage from idea conception to market launch and monitoring. In total, 38 models were scored against 41 criteria concerning model features, applicability, resource demands and outcome parameters. A scoring scheme was developed to determine how the models fit the criteria of each innovation stage. For each model, the individual criteria scores were added, yielding an overall fit score to each innovation stage. Three criteria were critical to stakeholders and incorporated as multipliers in the scoring scheme; the required time/costs and level of expertise needed to use the model, and for risk assessment models only, the option to compare PEC and PNEC. Regulatory compliance was also identified as critical, but could not be incorporated, as a nanomaterial risk assessment framework has yet to be developed and adopted by legislators. In conclusion, the scoring approach underlined similar scoring profiles across stages within model categories. As most models are research tools designed for use by experts, their score generally increased for later stages where most resources and expertise are committed. In contrast, stakeholders need relatively simple models to identify potential hazards and risk management measures at early product development stages to ensure safe use of nanomaterials without costs and resource needs hindering innovation.